Marine Protected Areas in Brazil: An ecological approach regarding the large marine ecosystems - Schiavetti, Alexandre; Manz, Jacques; Zapelini dos Santos, Cleverson; Magro, Teresa Cristina; Pagani, Maria Inez [UNESP] (Elsevier, 2013)
The objective of this study was to address the importance of implementing Coastal and Marine Protected Areas in Brazil and to examine their distribution, based on the delimitation of Large Marine Ecosystems. Out of a total of 336 protected areas identified in Brazilian coastal and marine areas, the North Platform has the largest protected area, but the ecosystem with the largest number of protected area, predominantly sustainable areas, was the East Coast followed by the South Platform. One of the reasons the eastern coast of Brazil to have more protected areas is the fact that there is a largest amount of coral reefs. Additionally there was political opportunities for the creation of protected areas for sustainable use. The coastal region of Brazil has achieved the goal proposed by the Seventh Conference of the Parties to the Convention on Biological Diversity - 7, but only then through the category V of the International Union for Conservation of Nature, which is not the best efficient means of conserving resources. The goal for marine conservation shows only the area above the recommended under protection in North Platform. The Marine portion of the East Coast and the South Platform has few protected areas, regardless of category management. We consider the coastal region the range of 12 nautical miles from baselines determined in accordance with the United Nations Convention on the Law of the Sea. As for the number of strategies permitted by law and used for the conservation of coastal and marine systems, coastal systems show a higher number when compared with the marine system. We suggest that the Brazilian government should specify strategies for the protection of marine systems and expand the protected areas of all Large Marine Ecosystems. © 2013 Elsevier Ltd.
Keywords: Category management; Coastal systems; Ecological approaches; Large marine ecosystem; Law of the seas; Marine conservations; Marine protected area; Protected areas; Coastal zones; Conservation; Ecosystems; Environmental protection; baseline survey; coastal zone management; coral reef; ecological approach; Law of the Sea; marine ecosystem; marine park; sustainability; Brazil